2013
DOI: 10.1111/1744-9987.12102
|View full text |Cite
|
Sign up to set email alerts
|

Serum Hepcidin Levels Are Associated With Serum Triglycerides and Interleukin‐6 Concentrations in Patients With End‐Stage Renal Disease

Abstract: Hepcidin has emerged as a peptide with a key role in the regulation of iron homeostasis in patients with chronic kidney disease (CKD), having a strong dependence on inflammation. Recent studies reveal that hepcidin may be also associated with the progression of atherosclerosis. This study was performed to analyze the relation of hepcidin to markers of atherosclerosis and inflammation in patients on dialysis. A total of 90 individuals were enrolled. Sixty patients with end-stage renal disease, who were on hemod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…Results of this study are consistent with the previous research [26]. Additionally, there is a positive correlation between serum hepcidin and hsCRP and IL-6 in MHD patients, indicating that the increase of serum hepcidin in MHD patients is related to the state of inflammation, as reported in a previous study [27]. Some studies have shown that IL-6 can regulate the expression of the hepcidin gene by the following mechanism: IL-6 can activate the transcription activator of ferritin by combining with signal transduction and transcription activator 3 (STAT3), thereby increasing the synthesis of hepcidin [28,29].…”
Section: Discussionsupporting
confidence: 93%
“…Results of this study are consistent with the previous research [26]. Additionally, there is a positive correlation between serum hepcidin and hsCRP and IL-6 in MHD patients, indicating that the increase of serum hepcidin in MHD patients is related to the state of inflammation, as reported in a previous study [27]. Some studies have shown that IL-6 can regulate the expression of the hepcidin gene by the following mechanism: IL-6 can activate the transcription activator of ferritin by combining with signal transduction and transcription activator 3 (STAT3), thereby increasing the synthesis of hepcidin [28,29].…”
Section: Discussionsupporting
confidence: 93%
“…However, neither IL-6 nor leptin was correlated with hepcidin during pregnancy. Positive correlations between IL-6 and hepcidin have been reported in patients with end-stage renal disease 37 and sepsis 38 but not in healthy premenopausal 11 or pregnant women. 5,32 The absence of positive relationships in individuals without severe inflammation may suggest that a threshold level of IL-6 must be reached to significantly impact hepcidin production.…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirmed our previous finding that ferritin and hepcidin-25 could be predictive factors for the response to OIT in HD patients in the absence of inflammation [ 25 ]. Serum levels of hepcidin-25 were positively correlated with triglycerides and interleukin (IL-6) and CRP in HD patients [ 47 , 48 ]. In addition, high serum levels of triglycerides were associated with hyporesponsiveness to IIT in HD patients [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…These factors can increase ferritin and hepcidin-25, leading to reduced iron availability for erythropoiesis [ 39 ]. In fact, serum levels of IL-6 were correlated with those of ferritin and hepcidin-25 in CKD patients [ 17 , 46 , 48 ]. Regardless of ferritin and inflammation markers (CRP and IL-6), the levels of anti-oxidant glutathione peroxidase in erythrocytes were lower in the IIT-nonresponders than in the IIT-responders [ 52 ].…”
Section: Discussionmentioning
confidence: 99%